2018
DOI: 10.30569/adiyamansaglik.433789
|View full text |Cite
|
Sign up to set email alerts
|

Ameliyathane Dışı Anestezi Uygulamalarımız. 3 Aylık Dönemdeki 2268 Hastanın Değerlendirilmesi.

Abstract: Bu çalışmada 2018 yılına ait 3 aylık dönemdeki ameliyathane dışı anestezi uygulaması yapılmış olguların retrospektif olarak incelenmesi amaçlandı. Materyal ve Metod: Afyon Devlet Hastanesi 2018 yılına ait 3 aylık dönemde alınan ameliyathane dışı anestezi kayıtları incelendi. Hastaların Amerikan Anesteziyologlar Birliği'nin fiziksel durum sınıflaması (ASA) skoru, yaş, cinsiyet, işlem sırasında kullanılan ilaçlar, komplikasyonlar ve yoğun bakım ihtiyacı gibi bilgileri kaydedildi. Bulgular: Ameliyathane dışı anes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…4,7,41 On the other hand, previous studies reported that there was a difference between the genders in terms of SA. In some studies, the rate of addiction was reported to be higher in females, 9,16,42 while other studies reported that the rate of addiction was higher in males than females. 2,17 In this study, the lack of a significant difference in terms of gender may be related to the lower number of male NSs.…”
Section: Discussionmentioning
confidence: 97%
“…4,7,41 On the other hand, previous studies reported that there was a difference between the genders in terms of SA. In some studies, the rate of addiction was reported to be higher in females, 9,16,42 while other studies reported that the rate of addiction was higher in males than females. 2,17 In this study, the lack of a significant difference in terms of gender may be related to the lower number of male NSs.…”
Section: Discussionmentioning
confidence: 97%
“…However, the transformation of this widespread use of smartphones to addiction has been reported to have negative effects on the feeling of satisfaction with life, happiness levels, and subjective well-being of young people (Kozan, Kavaklı, & Cutter, 2019;Çelik, 2018;Lepp, Barkley and Karpinski, 2014;Park and Lee, 2012). Apart from the stated psychological problems, hand and neck dysfunctions, headache, and poor sleep quality physiological problems are also among the negative effects of smartphone addiction (Sülün, Günay, Sarman and Dertli, 2020;Günal and Pekçetin, 2019;Koças and Şaşmaz, 2019;Randjelović, Stojiljković, Radulović, Stojanović and Ilić, 2019;Keskin Ergan, Başkurt and Başkurt, 2018;Yorulmaz, Kıraç and Sabırlı, 2018;Demirci, Akgönül and Akpınar, 2015).…”
Section: Introductionmentioning
confidence: 99%